Allergenic Characterization of a Novel Allergen, Homologous to Chymotrypsin, from German Cockroach - Jeong, Kyoung Yong; Son, Mina; Lee, Jae-Hyun; Hong, Chein-Soo; Park, Jung-Won (Allergy, asthma & immunology research, 2015)
Cockroach feces are known to be rich in IgE-reactive components. Various protease allergens were identified by proteomic analysis of German cockroach fecal extract in a previous study. In this study, we characterized a novel allergen, a chymotrypsin-like serine protease. A cDNA sequence homologous to chymotrypsin was obtained by analysis of German cockroach expressed sequence tag (EST) clones. The recombinant chymotrypsins from the German cockroach and house dust mite (Der f 6) were expressed in Escherichia coli using the pEXP5NT/TOPO vector system, and their allergenicity was investigated by ELISA. The deduced amino acid sequence of German cockroach chymotrypsin showed 32.7 to 43.1% identity with mite group 3 (trypsin) and group 6 (chymotrypsin) allergens. Sera from 8 of 28 German cockroach allergy subjects (28.6%) showed IgE binding to the recombinant protein. IgE binding to the recombinant cockroach chymotrypsin was inhibited by house dust mite chymotrypsin Der f 6, while it minimally inhibited the German cockroach whole body extract. A novel allergen homologous to chymotrypsin was identified from the German cockroach and was cross-reactive with Der f 6.